Harnessing the potentialities of probiotics, prebiotics and synbiotics application for agriculture industry: A mini review - Siti Zulaiha, Zailani; Nurin Syakirah, Abd Rahim; Aizi Nor Mazila, Ramli (UTM Press, 2024)
The agricultural industry significantly drives global economic growth. However, the undeniable impacts of intensive use of chemical fertilizers, pesticides, and intensified farming practices contribute to soil erosion. Synbiotics, a combination of prebiotic and probiotic offer an alternative approach to preserve and improve the quality of soil. The main objective of this review is to provide comprehensive overview of the application of the synbiotic approach to the productivity of the agriculture. The review covers soil fertility factors, as well as the roles of synbiotic, prebiotic and probiotic in enhancing the growth of plant in agriculture. Biofertilizers, consisting of organic matter and beneficial microbes, establish a symbiotic relationship with plants, enhancing both soil health and plant growth. The combination of probiotic and prebiotic can generate high production of agriculture yield.